Development of Competency Test for Cluster Scheme of Information System-Based Network Cable Installation (Journal of Vocational and Career Education, 2022)
Covid 19 pandemic influenced the learning process and brought traditional classes to online classes. This condition made the XI grade of Computer Networking students got difficulty in the examination at school.  The students were not ready because of the absence of learning media that provided students with the material. The current research aimed to develop and analyse the feasibility, practicality, and also effectiveness of information systems for XI-grade students of Computer Engineering and Networking. The researcher adopted RnD with the ADDIE approach, and twenty students became the participants of the research. Media experts and material experts were involved in examining the product. An information system was implemented in the first group of the networking installation subject.    The data collection used need analysis, the feasible test questionnaire of information system, pre-test, and post-test. The researcher applied mean, percentage descriptive analysis, Paired sample t-Test, and N-Gain as data analysis of the research.  The result showed 1) the feasible test of information system achieved 4,79 for the media, or it was categorized as very feasible. Furthermore, the product gained 4,71 for the material, or it said very feasibly. 2) The practicality of the information system showed an overall average score was 97% of the practicality criteria. 3) Information system media was declared effective in increasing students’ competency with an average N-gain score achieved 73% or stated as quite effective.